Review Study on Piezoelectric Energy Harvesters and Their Applications - Dixit, NK; Rangra, KJ; Sharma, YC (International Journal of Computer Sciences and Engineering, 2025)
To minimize the requirement of external power source and maintenance for electric devices such as wireless sensor networks, the energy harvesting technique based on vibrations has been a dynamic field of studying interest over past years. This presents a challenge for the researchers to optimize the energy output of piezoelectric energy harvesters, due to the relatively high elastic moduli of piezoelectric materials used to date. This paper reviews the current state of research on piezoelectric energy harvesting devices for low frequency (0–100Hz) applications. Various key aspects that contribute to the overall performance of a piezoelectric energy harvester are discussed.